Adenosine Dependent Anti-Inflammatory Effects of Arrabidaea Chica VERLOT - Ubiera, Rosmery Duran (2021)
Arrabidaea Chica (Bigonnnace) is commonly used in The Amazon by folks due to its anti-inflammatory properties, properties that have been confirmed in different experimental models of disease, but the molecular processes that govern this effect were unclear. The immune system mediates inflammation through a variety of mechanisms, including the production of pro-inflammatory and anti-inflammatory cytokines, which are directed by different signaling pathways, among them the adenosinergic pathway. The study of new antiinflammatory molecules provides a long-term solution to the global problem that represents inflammation when uncontrolled and the Amazon is rich in natural products that need to be studied. The objective of this study was to elucidate whether or not the anti-inflammatory effect of Arrabidaea Chica VERLOT in bone marrow-derived macrophages (BMDM) is mediated by adenosine. The production of pro-inflammatory (IL-1β and TNFα) and anti-inflammatory (IL-10) cytokines, was assessed by ELISA in the supernatant of BMDM preincubated with Arrabidaea ChicaVERLOT aqueous extract and stimulated with LPS. Arrabidaea Chica demonstrated to decrease the production of IL-1β and increase the production of IL-10. The increased production of IL-10 was associated with elevated production of adenosine and this effect was not observed when the different steps of the adenosinergic pathway were pharmacologically inhibited or genetically suppressed. The participation of the metabolism of the cells was also confirmed as the direct source of ATP for the generation of adenosine. We conclude that Arrabidaea Chica VERLOT mediates its anti-inflammatory effect via the adenosinergic pathway, increasing the metabolic rate of the cells to generate the substrate for this pathway.